1999
DOI: 10.1104/pp.119.3.859
|View full text |Cite
|
Sign up to set email alerts
|

A Single Limit Dextrinase Gene Is Expressed Both in the Developing Endosperm and in Germinated Grains of Barley1

Abstract: The single gene encoding limit dextrinase (pullulan 6-glucanohydrolase; EC 3.2.1.41) in barley (Hordeum vulgare) has 26 introns that range in size from 93 to 822 base pairs. The mature polypeptide encoded by the gene has 884 amino acid residues and a calculated molecular mass of 97,417 D. Limit dextrinase mRNA is abundant in gibberellic acid-treated aleurone layers and in germinated grain. Gibberellic acid response elements were found in the promoter region of the gene. These observations suggest that the enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 59 publications
(94 reference statements)
4
46
0
Order By: Relevance
“…High expression levels in endosperm tissues were also found for the genes encoding SUSIBA2 (HvWRKY46) and limit dextrinase (HvLD), confirming earlier findings (Burton et al, 1999;Sun et al, 2003). The diurnally fluctuating transcripts for HvWRKY41 (Mangelsen et al, 2008) could mainly be detected in endosperm and pericarp tissues.…”
Section: Quantification Of Spatial Gene Expressionsupporting
confidence: 75%
See 1 more Smart Citation
“…High expression levels in endosperm tissues were also found for the genes encoding SUSIBA2 (HvWRKY46) and limit dextrinase (HvLD), confirming earlier findings (Burton et al, 1999;Sun et al, 2003). The diurnally fluctuating transcripts for HvWRKY41 (Mangelsen et al, 2008) could mainly be detected in endosperm and pericarp tissues.…”
Section: Quantification Of Spatial Gene Expressionsupporting
confidence: 75%
“…7). As reported earlier (Sun et al, 1998;Burton et al, 1999;Radchuk et al, 2009), the transcripts of HvSBEIIb and HvLD were mainly found in the endosperm and are thus likely to be involved in the biosynthesis of storage starch (Table I; Fig. 8).…”
Section: Diurnal Regulation Of Starch Metabolism and Sugar Signalingmentioning
confidence: 54%
“…Three SBE cDNAs were identified, each almost identical with the cloned SBEI (Mutisya et al, 2003) and SBEIIa and SBEIIb (Sun et al, 1998) transcripts. Three different ISA cDNA sequences, one full and two partial, were identified, while one partial sequence was homologous with PUL cDNA (Burton et al, 1999(Burton et al, , 2002a. We did not find another PUL gene (Kristensen et al, 1999) among the seed-specific ESTs, possibly because of its preferential expression during seed germination.…”
Section: Localization Of Starch In the Developing Barley Grainmentioning
confidence: 75%
“…Starch granule initiation and growth are altered in a barley mutant lacking ISA activity (Burton et al, 2002a). The PUL gene is expressed in both the developing barley endosperm and the germinating caryopsis, indicating its potential function for starch modification during synthesis and for starch hydrolysis during germination (Burton et al, 1999;Dinges et al, 2003).…”
mentioning
confidence: 99%
“…3). Given that ␣-amylase and β-glucanase belong to a group of hydrolases synthesised by aleurone cells in response to gibberellin 12 , these increases are likely to be accompanied by increases in the production of other hydrolases synthesised by the aleurone in response to gibberellin, such as ␣-glucosidase 13 , limit dextrinase 7 and proteases 8 , all of which would contribute to improved malt performance within the brewery.…”
Section: Enzyme Production and Malt Qualitymentioning
confidence: 99%